The role of TNF receptors as mediators of chronic vasculitis in possible milder forms of the CNS tuberculosis - Rivas-Castro, Alejandro; Salinas-Lara, Citlaltepetl; Sánchez Garibay, Carlos; Abarca-Rojano, Edgar; Hernández-Pando, Rogelio; Marquina-Castillo, Brenda; Flores Barrada, Manuel Alejandro; Peralta-Díaz, Yazmín; León-Marroquín, Elsa Yazmín; Tena Suck, Martha Lilia; Medina Mendoza, Jessica; Sánchez Gama, Yaser; et al. (The Journal of Infection in Developing Countries, 2023)
Introduction: Central nervous system (CNS) tuberculosis (TB) is the most severe form of TB due to its high mortality and functional sequelae. There are several differential diagnoses for TB; and, it can also cause secondary conditions, such as vasculitis. Methodology: 155 biopsies, corresponding to 155 different patients out of 5,386 registered biopsies from 2008-2013, met the criteria of unknown etiology vasculitis and evidence of cerebral vascular disease. These were analyzed to assess the presence of central nervous system TB. The selected cases were assessed with Suzaan Marais (SM) criteria for clinical tuberculosis. After that, Ziehl-Neelsen (ZN) staining and polymerase chain reaction (PCR) were performed to amplify a fragment of the insertion sequence IS6110 of M. tuberculosis. 21 patients met the criteria for definitive tuberculosis by ZN staining and PCR, and 2 met the criteria for possible tuberculosis. Tumor necrosis factor (TNF)-α, TNF-R1, and TNF-R2 were determined by immunohistochemistry in histological sections from formalin-fixed paraffin-embedded (FF-PE) tissues in the 23 selected patients. Results: Granulomatous TB was present in almost half of the cases. TNF-R1 and TNF-R2 were expressed mainly in blood vessels, histiocytes, and macrophages. TNF-R2 expression was higher than the other markers, which suggests an anti-inflammatory response against M. tuberculosis Conclusions: The histopathological presentation of TB is not always limited to granulomas, abscesses, or meningitis; there are also clinical presentations characterized only with chronic inflammation of nervous and vascular tissue.